Molecular predictors of response and survival in patients with relapsed/refractory acute myeloid leukemia following venetoclax plus hypomethylating agent therapy - Isla M. Johnson; Rimal Ilyas; Kristen McCullough; Aref Al-Kali; Hassan B. Alkhateeb; Kebede H. Begna; Abhishek Mangaonkar; Antoine Saliba; Mark R. Litzow; William Hogan; Mithun Shah; Mrinal M. Patnaik; et al. (Haematologica)
Not available.